ANALISIS VALUE CHAIN SYSTEM DAN STRATEGY PEMASARAN RUMPUT LAUT DI KABUPATEN MALUKU TENGGARA (Analyze Value Chain System and Seaweed Marketing Strategy in North East Maluku District) - Anna Maria Ngabalin (IPB University, 2014)
Potential land in Southeast Maluku regency, Maluku Province, is one of the means in the seaweed cultivation and production. Additionally, as most people work as fishermen, theireconomic situation is getting improved although it is not yetin accordance with the target of maximum achievement at the level of life necessities. To increase the production and marketing of seaweed, this study usedthe Value Chain System which analyzedmain activities include the process of Nurseries, Operations, Logistics and phase of marketing and sales which are supported by Infrastructure, Human Resource Management, and Development of Seaweed Technology. In the description of the Value Chain, theanalysisof added-valuewas also performed on each main actor with a value of Rp. 288 to fishermen, Rp. 550 to Small Scale Traders, and Rp.850 to LargeScale Traders. The determination of the marketing strategy using SWOT analysis (Strengths, Weaknesses, Opportunities and Threats) produced the alternative marketing strategies in strategy formulation. It was concluded based on internal and external factors in the seaweed production and marketing processes. In this context, the analysis of the value chain system was critical to improve the market access and to ensure a more efficient flow of products, as well asto ensure that all actors benefit proportionally, according to their contributions.Keywords: Value Chain, Seaweed Marketing, SWOT